High-performance low-residual-stress Cu-Ni-Co-Si alloy sheet and preparation method thereof
Patent Information
- Application Number
- CN202611394139.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]本发明的目的在于提供一种高性能低残余应力Cu-Ni-Co-Si合金板材及其制备方法,以解决现有Cu-Ni-Co-Si合金难以同时兼顾高强度、高导电性、优异折弯加工性能以及低残余应力的技术问题
本发明通过添加Ni、Co、Si并严格控制Ni与Co的比例以及(Ni+Co)与Si的比例,实现协同沉淀强化,在提升合金强度的同时保持优异的导电率;通过添加Mg、Ti及稀土元素,在进一步提升强度与硬度的同时,发挥晶粒细化作用,优化合金组织均匀性,提高折弯性能,从解决了传统Cu-Ni-Co-Si合金强度与加工性能难以兼顾的矛盾;
Smart Images

Figure CN122879548A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of copper alloy materials technology, specifically relating to a high-performance, low residual stress Cu-Ni-Co-Si alloy plate and its preparation method. Background Technology
[0002] With the rapid development of 5G communication, new energy vehicles, and precision electronics industries, core components such as connectors, relay springs, and lead frames are moving towards miniaturization, high integration, and long lifespan. This places synergistic performance requirements on copper-based structural functional materials, namely "high strength, high conductivity, and excellent processability." On the one hand, they need to have sufficiently high tensile strength (≥990MPa) and yield strength (≥940MPa) to resist stress relaxation during service. On the other hand, they need to ensure conductivity of over 36% IACS to achieve efficient signal and energy transmission in high-frequency and high-current scenarios. At the same time, they also need to meet the processing requirements of complex forming, such as the ultimate bending performance of 90° bending with R / t=0.
[0003] Cu-Ni-Co-Si alloys rely on the core role of the (Ni,Co)2Si precipitation strengthening phase to become one of the preferred material systems that take into account the above performance requirements. The strengthening mechanism is based on the synergistic effect of precipitation strengthening, grain refinement strengthening and work hardening. The alloy performance is highly dependent on the precise ratio of elements such as Ni, Co and Si, as well as the synergistic control of multiple processes such as hot rolling, cold rolling, solution treatment, aging and low temperature tension annealing.
[0004] However, existing Cu-Ni-Co-Si alloys generally suffer from poor performance stability in actual production. In terms of composition design, an excess or imbalance in the proportions of any element such as Ni, Co, or Si can easily lead to a large number of solute atoms dissolved in the matrix, resulting in a sharp drop in the alloy's conductivity and strength. Regarding process control, even minor deviations in cold rolling rate, solution temperature and speed, aging temperature and time, and low-temperature tension annealing parameters can alter grain size and the quantity, size, and dispersion of precipitates, causing the alloy's performance to deviate from the target range and making it difficult to consistently meet product performance requirements. Furthermore, the optimization of bending performance in existing Cu-Ni-Co-Si alloys largely relies on individual adjustments to subsequent process parameters such as solution treatment, cold rolling, aging, and tension leveling. It has not yet been able to control residual stress within ±50MPa while simultaneously achieving the ultimate bending performance of 90° bending with R / t=0, while ensuring tensile strength ≥990MPa, yield strength ≥940MPa, and conductivity ≥36%IACS.
[0005] Therefore, how to coordinate and optimize multiple dimensions such as composition design, process control and microstructure control to develop a Cu-Ni-Co-Si alloy plate and its preparation method that can simultaneously take into account high strength, high conductivity, excellent processing performance and low residual stress is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] The purpose of this invention is to provide a high-performance, low-residual-stress Cu-Ni-Co-Si alloy sheet and its preparation method, so as to solve the technical problem that existing Cu-Ni-Co-Si alloys are difficult to simultaneously achieve high strength, high conductivity, excellent bending performance and low residual stress.
[0007] To achieve the above objectives, the first aspect of the present invention provides a high-performance, low-residual-stress Cu-Ni-Co-Si alloy sheet, wherein the chemical composition of the alloy sheet by weight percentage is: Ni 2.3%~4.6%, Co 0.1%~0.8%, Si 0.6%~1.3%, Mg 0.01%~0.12%, Ti 0.01%~0.025%, rare earth elements 0~0.1% (rare earth elements are one or more of La, Ce, and Y), and the balance is Cu and unavoidable trace impurities; and satisfies (Ni+Co) / Si=4~4.2.
[0008] Preferably, the thickness of the alloy plate is 0.03~0.8mm, more preferably 0.05~0.8mm, and the width is 550~600mm; the specifications of the ingot used to prepare the alloy plate are: width ≥610mm and thickness ≥150mm.
[0009] Preferably, the alloy sheet undergoes aging treatment to precipitate a second phase inside, followed by cold rolling to cause a large number of internal dislocations to multiply. The dislocations interact with the second phase to form a stable dislocation cell structure, thereby enabling the alloy sheet to simultaneously obtain high strength and good plasticity.
[0010] Preferably, the alloy sheet has a hardness of 270~330HV, conductivity ≥36%IACS, grain size ≤0.01mm, tensile strength ≥990MPa, yield strength ≥940MPa, R / t ≤0.5 in the GW and BW directions of a 90° bend, R / t ≤2.5 in the GW and BW directions of a 180° bend, residual stress controlled within ±50MPa, and a smooth surface free from defects such as inclusions, pores, and cracks.
[0011] The second aspect of this invention provides a method for preparing the above-mentioned high-performance, low-residual-stress Cu-Ni-Co-Si alloy sheet, including processes such as smelting, casting, hot rolling, cold rolling, online solution treatment, aging, and low-temperature tension annealing, specifically including the following steps: S1. Ingredients: Prepare the raw materials according to the above weight percentages; S2. Smelting: First, lay a layer of pure copper at the bottom, then add electrolytic copper plates and pure cobalt, along with a slag remover. After the copper molten metal is fully melted, cover it with graphite powder, then add a small amount of copper-magnesium master alloy with a magnesium content of 20wt% for deoxidation. Next, add all the prepared copper-silicon master alloy with a silicon content of 20wt%. Heat to the smelting temperature of 1200~1300℃, stir for 3~5 minutes, let stand for 10~15 minutes, then take a sample for composition analysis and adjust the composition according to the results. After composition adjustment, remove slag and degas for 20~30 minutes, then let stand for another 10~15 minutes before starting casting. S3. Casting: The crystallizer is made of copper or graphite; the casting speed is 70~110 mm / min; the casting temperature is 1200~1250℃; and the primary cooling water flow rate is 40~70 m³ / min. 3 / h, secondary cooling water flow rate 4~7m 3 / h; During the casting process, a titanium ladle with a titanium content of 30wt% and the aforementioned rare earth elements are continuously added to the flow channel to obtain an ingot; S4. Sawing: Cut the head of the ingot by about 200~400mm to reduce cracking and poor surface quality during subsequent rolling. S5. Hot rolling: The ingot is heated in a walking beam furnace from room temperature to 950~1050℃, held for 3~5 hours, and the furnace exit temperature is 840~880℃. It is rolled 7~9 times, and the final rolling temperature is 600~750℃. The total processing rate is 90%~95%, and hot-rolled strip is obtained. S6. Milling: Mill the surface of the strip obtained after hot rolling. Mill 0.5~1.5mm on the top and bottom sides and 0.3~1.0mm on the width sides to ensure that there are no defects on the surface after milling. S7. Cold rolling: Cold rolling is performed on the milled strip blank, with a processing rate of approximately 85% to 90%. S8. Trimming: Trim the edges of the cold-rolled strip blank, cutting about 5-10mm on each side to obtain the trimmed strip. Ensure that all edge cracks are completely removed to avoid strip breakage during subsequent processing. S9. Low-temperature tension annealing before solution treatment: The strip after edge trimming is subjected to low-temperature tension annealing treatment at a temperature of 350~450℃, a speed of 15~45m / min, and a tension of 2~9kg / mm. 2 ; S10, One-time online solution treatment: The strip after step S9 is subjected to high-temperature solution treatment. The strip passes through at a speed of 5-35 m / min in a temperature range of 950-1100℃ and is then rapidly cooled to obtain a supersaturated solid solution. S11. Cold rolling: The solution-treated strip is further cold-rolled, with the cold rolling rate controlled at 30%~80%. S12, Secondary online solution treatment: The strip after cold rolling in step S11 is then subjected to online solution treatment at a temperature of 650~850℃ and a speed of 60~90m / min. S13. Aging: The strip after solution treatment in step S12 is subjected to aging treatment at a temperature of 400~500℃ for 6~12 hours. S14. Cleaning: Clean the aged coil to remove surface oxide scale; S15. Cold rolling: Cold rolling is performed on the cleaned coils, with a processing rate of 15%~40%; S16. Low-temperature tension annealing of finished product: The coil after cold rolling in step S15 is subjected to low-temperature tension annealing at a temperature of 350~500℃, a speed of 30~55m / min, and a tension of 4~9kg / mm. 2 Finally, the high-performance, low residual stress Cu-Ni-Co-Si alloy plate was obtained.
[0012] In summary, this application has the following beneficial effects: This invention achieves synergistic precipitation strengthening by adding Ni, Co, and Si and strictly controlling the ratio of Ni to Co and the ratio of (Ni+Co) to Si, thereby improving the alloy strength while maintaining excellent conductivity. By adding Mg, Ti, and rare earth elements, it further enhances the strength and hardness while refining the grains, optimizing the uniformity of the alloy structure, and improving bending performance, thus resolving the contradiction between the strength and processing performance of traditional Cu-Ni-Co-Si alloys. This invention introduces a low-temperature tension annealing process before the first solution treatment, allowing the material rolled at a high processing rate to be in a recovery state before recrystallization before entering the high-temperature solution treatment. This rearranges and partially cancels out point defects and dislocations within the material, gradually releasing unevenly stored deformation energy and reducing the overall driving force of the subsequent high-temperature solution treatment, resulting in more uniform grain size. Simultaneously, a two-stage online solution treatment is employed. The first stage uses high-temperature treatment to bring the material to a supersaturated state, ensuring sufficient precipitation during subsequent aging to achieve higher performance. The second stage uses a low-temperature, rapid process, preventing the material from precipitating a second phase and controlling the grain size to ≤0.01mm. Fine and uniform grains effectively improve the material's strength and plasticity. Finally, high-tension low-temperature annealing is used in the finished product stage. Under the synergistic effect of temperature and tension, the residual stress of the copper strip is controlled within ±50MPa, effectively suppressing the twisting and deformation problems of the ultra-high-strength copper alloy during the stamping process. The present invention, through the synergistic processing of the above-mentioned smelting, casting, hot rolling, solution treatment, aging, cold deformation, and low-temperature tension annealing, finally obtains Cu-Ni-Co-Si alloy plates with a thickness of 0.05~0.8mm, a hardness of 270~330HV, a conductivity ≥36%IACS, a grain size ≤0.01mm, a tensile strength ≥990MPa, a yield strength ≥940MPa, a 90° bend R / t ≤0.5 in the GW and BW directions, a 180° bend R / t ≤2.5 in the GW and BW directions, and a smooth plate surface free from defects such as inclusions, pores, and cracks. Attached Figure Description
[0013] Figure 1 This is a transmission electron microscope (TEM) image of the dislocation cell structure formed by the interaction between the second phase and dislocations after aging and cold rolling according to the present invention.
[0014] Figure 2 This is a transmission electron microscope (TEM) image of the microstructure of a copper alloy plate. Detailed Implementation
[0015] The present invention will be further described in detail below with reference to specific embodiments. However, the implementation of the present invention is not limited thereto. Various changes and modifications can be made by those skilled in the art without departing from the spirit and essence of the present invention, and all such changes and modifications fall within the scope of protection claimed by the present invention.
[0016] In this invention, the functions of each added element in the Cu-Ni-Co-Si alloy are as follows: Ni is one of the most critical elements in Cu-Ni-Co-Si alloys. Its core role is to form the Ni₂Si precipitate strengthening phase with Si. The coherent relationship between Ni₂Si and the Cu matrix effectively hinders dislocation slip. This dispersed second phase is a key factor determining the alloy's strength, elasticity, and electrical conductivity. When the Ni content is insufficient, the Ni₂Si phase precipitation is inadequate, significantly weakening the strengthening effect. When the Ni content is too high, some Ni cannot combine with Si and remains in the Cu matrix in a solid solution state, leading to a significant decrease in the alloy's electrical conductivity and coarser precipitates, but the strength will be improved.
[0017] The atomic radii of Co and Ni are almost identical (Ni: 0.124 nm, Co: 0.125 nm), allowing Co to completely dissolve in the Ni₂Si phase to form a (Ni,Co)₂Si solid solution. This solid solution substitution produces the following effects: First, it refines the size of the Ni₂Si phase, resulting in higher dispersion and a more significant strengthening effect. Second, it enhances the stability of the phase; the lattice energy of the (Ni,Co)₂Si phase is higher than that of pure Ni₂Si, reducing the coarsening rate by 60%–70% at high temperatures and preventing strength decay caused by over-aging. Third, it improves the phase's resistance to dislocation cutting; Co has a higher atomic number and stronger bond energy with Si, increasing the hardness of the (Ni,Co)₂Si phase by 15%–20%, requiring more energy to cut through the particles due to dislocations.
[0018] Si is an essential element for the formation of Ni2Si and (Ni,Co)2Si precipitates. Without Si, the core strengthening phase cannot be formed. At the same time, the Si content directly determines the amount, size and distribution of Ni2Si and (Ni,Co)2Si precipitates, and plays a quantitative control role in the alloy properties. Si has little effect on electrical conductivity after precipitation, which is one of the key reasons why Cu-Ni-Co-Si alloys can achieve both high strength and high conductivity.
[0019] Mg has limited solid solubility in a copper matrix, primarily enhancing the strength and hardness of copper alloys through solid solution strengthening mechanisms without significantly impairing their electrical conductivity. The size difference between Mg and Cu atoms introduces lattice distortion, hindering dislocation movement and thus increasing yield strength. More importantly, Mg significantly inhibits recrystallization during annealing of copper sheets and strips, raising the recrystallization temperature and enhancing the material's high-temperature softening resistance.
[0020] Ti also exhibits solid solution strengthening effects in copper, but its more important mechanisms lie in precipitation strengthening and grain refinement. Ti can effectively refine the as-cast grains, reduce casting defects such as shrinkage porosity and segregation, and improve the processing plasticity and surface quality of copper strips. During subsequent heat treatment, Ti can also form metastable precipitates such as Cu3Ti or Cu4Ti with Cu, producing a strong precipitation strengthening effect during the aging stage, enabling copper strips to achieve higher strength and maintain good electrical conductivity.
[0021] Rare earth elements (La, Ce, Y) are chemically very reactive and have a much stronger affinity for harmful elements such as oxygen and sulfur than copper. During the smelting process, rare earth elements can preferentially combine with impurities such as oxygen and sulfur to form high-melting-point rare earth compounds that float to the surface of the melt and are removed. Rare earth elements can also reduce the segregation of harmful impurities at grain boundaries, making the grain boundaries purer. The purified matrix and grain boundaries reduce electron scattering, which can significantly improve the conductivity of the alloy.
[0022] The second aspect of this invention provides a method for preparing the above-mentioned high-performance, low-residual-stress Cu-Ni-Co-Si alloy sheet, including processes such as smelting, casting, hot rolling, cold rolling, online solution treatment, aging, and low-temperature tension annealing, specifically including the following steps: S1. Ingredients: Prepare the raw materials according to the above weight percentages; S2. Smelting: First, lay a layer of pure copper at the bottom, then add electrolytic copper plates and pure cobalt, add slag remover, and after the copper is fully smelted, cover with graphite powder, then add a small amount of copper-magnesium master alloy (magnesium content 20wt%) for deoxidation, and then add all the prepared copper-silicon master alloy (silicon content 20wt%). Raise the temperature to the smelting temperature of 1200~1300℃, stir for 3~5 minutes, let stand for 10~15 minutes, take a sample for composition analysis, and adjust the composition according to the analysis results; after composition adjustment, remove slag and degas for 20~30 minutes, let stand for another 10~15 minutes, and then start casting; S3. Casting: The crystallizer is made of copper or graphite; the casting speed is 70~110 mm / min; the casting temperature is 1200~1250℃; and the primary cooling water flow rate is 40~70 m³ / min. 3 / h, secondary cooling water flow rate 4~7m 3 / h; During the casting process, titanium flasks (titanium content 30wt%) and the aforementioned rare earth elements are continuously added to the flow channel to obtain ingots; S4. Sawing: Cut the head of the ingot by about 200~400mm to reduce cracking and poor surface quality during subsequent rolling. S5. Hot rolling: The ingot is heated in a walking beam furnace from room temperature to 950~1050℃, held for 3~5 hours, and the furnace exit temperature is 840~880℃. It is rolled 7~9 times, and the final rolling temperature is 600~750℃. The total processing rate is 90%~95%, and hot-rolled strip is obtained. S6. Milling: Mill the surface of the strip obtained after hot rolling. Mill 0.5~1.5mm on the top and bottom sides and 0.3~1.0mm on the width sides to ensure that there are no defects on the surface after milling. S7. Cold rolling: Cold rolling is performed on the milled strip blank, with a processing rate of approximately 85% to 90%. S8. Trimming: Trim the edges of the cold-rolled strip blank, cutting about 5-10mm on each side to ensure that all edge cracks are completely removed and to avoid strip breakage during subsequent processing. S9. Low-temperature tension annealing before primary solution treatment: Low-temperature tension annealing is performed on copper strips after high-processing cold rolling at a temperature of 350~450℃, a speed of 15~45m / min, and a tension of 2~9kg / mm. 2 ; S10, One-time online solution treatment: The strip after step S9 is subjected to high-temperature solution treatment. The strip passes through at a speed of 5-35 m / min in a temperature range of 950-1100℃ and is then rapidly cooled to obtain a supersaturated solid solution. S11. Cold rolling: The solution-treated strip is further cold-rolled, with the cold rolling rate controlled at 30%~80%. S12, Secondary online solution treatment: The strip after cold rolling in step S11 is then subjected to online solution treatment at a temperature of 650~850℃ and a speed of 60~90m / min. S13. Aging: The strip after solution treatment in step S12 is subjected to aging treatment at a temperature of 400~500℃ for 6~12 hours. S14. Cleaning: Clean the aged coil to remove surface oxide scale; S15. Cold rolling: Cold rolling is performed on the cleaned coils, with a processing rate of 15%~40%; S16. Low-temperature tension annealing of finished product: The coil after cold rolling in step S15 is subjected to low-temperature tension annealing at a temperature of 350~500℃, a speed of 30~55m / min, and a tension of 4~9kg / mm. 2 Finally, the high-performance, low residual stress Cu-Ni-Co-Si alloy plate was obtained.
[0023] Example 1:
[0024] Ingredients: Raw materials are formulated according to the required weight ratio: Ni: 2.3%, Co: 0.1%, Si: 0.6%, Mg: 0.01%, Ti: 0.01%, and rare earth elements 0% (not added).
[0025] Smelting: First, add copper as a base, then add electrolytic copper plates and pure cobalt, followed by a slag remover. Once the molten copper is fully melted, cover with graphite powder. Then, add a small amount of copper-magnesium master alloy (20wt% magnesium content) for deoxidation, followed by the complete set of copper-silicon master alloy (20wt% silicon content). Heat to the smelting temperature of 1200℃, stir for 5 minutes, let stand for 15 minutes, take samples for composition analysis, and adjust the composition according to the analysis results. After composition adjustment, remove slag, degas for 30 minutes, let stand for 15 minutes, and then begin casting.
[0026] Casting: The crystallizer is made of copper or graphite; the casting speed is 70 mm / min; the casting temperature is 1200℃; and the primary cooling water flow rate is 70 m³ / min. 3 / h, secondary cooling water flow rate 7m 3 / h, during the casting process, titanium flasks (titanium content 30wt%) and rare earth elements are continuously added to the flow channel.
[0027] Sawing: Cut approximately 400mm from the top of the ingot.
[0028] Hot rolling: The ingot is heated in a walking beam furnace from room temperature to 950°C, held for 3 hours, and exited at 840°C. It is rolled in 7 passes and the final rolling temperature is 750°C. The total processing rate is 95%.
[0029] Milling: The strip obtained after hot rolling is milled, with 1.5 mm milled on the top and bottom sides and 1.0 mm milled on the width sides.
[0030] Cold rolling: The strip blank after milling is cold rolled, with a processing rate of about 90%.
[0031] Trimming: Trim the edges of the cold-rolled strip by about 5mm on each side.
[0032] Low-temperature tension annealing before solution treatment: temperature 450℃, speed 45m / min, tension 5kg / mm 2 .
[0033] One-time online solution treatment: The strip passes through at a speed of 35 m / min within a temperature range of 1100℃ and is rapidly cooled to obtain a supersaturated solid solution.
[0034] Cold rolling: The solution-treated strip is further cold rolled, with the cold rolling rate controlled at 50%.
[0035] Secondary online solution treatment: The solution temperature is 850℃ and the speed is 90m / min to obtain the final product.
[0036] Aging: After solution treatment, aging is carried out at 500℃ for 6 hours.
[0037] Cleaning: Clean the aged rolls to remove the surface oxide scale.
[0038] Cold rolling: The cleaned coil is cold rolled, with a processing rate of 25%.
[0039] Low-temperature tension annealing of finished products: temperature 500℃, speed 55m / min, tension 9kg / mm 2 The high-performance, low residual stress Cu-Ni-Co-Si alloy plate of Example 1 was obtained.
[0040] Example 2:
[0041] Ingredients: Raw materials are prepared according to the required weight ratio: Ni: 4.6%, Co: 0.8%, Si: 1.3%, Mg: 0.12%, Ti: 0.025%, and rare earth elements: 0.1%.
[0042] Smelting: First, add copper as a base, then add electrolytic copper plates and pure cobalt, followed by a slag remover. Once the molten copper is fully melted, cover with graphite powder. Then, add a small amount of copper-magnesium master alloy (20wt% magnesium content) for deoxidation, followed by the complete set of copper-silicon master alloy (20wt% silicon content). Heat to the smelting temperature of 1200℃, stir for 5 minutes, let stand for 15 minutes, take samples for composition analysis, and adjust the composition according to the analysis results. After composition adjustment, remove slag, degas for 30 minutes, let stand for 15 minutes, and then begin casting.
[0043] Casting: The crystallizer is made of copper or graphite; the casting speed is 70 mm / min; the casting temperature is 1200℃; and the primary cooling water flow rate is 70 m³ / min. 3 / h, secondary cooling water flow rate 7m 3 / h, during the casting process, titanium flasks (titanium content 30wt%) and rare earth elements are continuously added to the flow channel.
[0044] Sawing: Cut approximately 400mm from the top of the ingot.
[0045] Hot rolling: The ingot is heated in a walking beam furnace from room temperature to 950°C, held for 3 hours, and exited at 840°C. It is rolled in 7 passes and the final rolling temperature is 750°C. The total processing rate is 95%.
[0046] Milling: The strip obtained after hot rolling is milled, with 1.5 mm milled on the top and bottom sides and 1.0 mm milled on the width sides.
[0047] Cold rolling: The strip blank after milling is cold rolled, with a processing rate of about 90%.
[0048] Trimming: Trim the edges of the cold-rolled strip by about 5mm on each side.
[0049] Low-temperature tension annealing before solution treatment: temperature 350℃, speed 15m / min, tension 2kg / mm 2 .
[0050] One-time online solution treatment: The strip passes through at a speed of 5 m / min within a temperature range of 950℃ and is rapidly cooled to obtain a supersaturated solid solution.
[0051] Cold rolling: The solution-treated strip is further cold rolled, with the cold rolling rate controlled at 50%.
[0052] Secondary online solution treatment: The solution temperature is 650℃ and the speed is 60m / min to obtain the final product.
[0053] Aging: After solution treatment, aging is carried out at 400℃ for 12 hours.
[0054] Cleaning: Clean the aged rolls to remove the surface oxide scale.
[0055] Cold rolling: The cleaned coil is cold rolled, with a processing rate of 25%.
[0056] Low-temperature tension annealing of finished products: temperature 350℃, speed 30m / min, tension 4kg / mm 2 Thus, the high-performance, low residual stress Cu-Ni-Co-Si alloy plate of Example 2 was obtained.
[0057] Example 3:
[0058] Ingredients: Raw materials are prepared according to the required weight ratio: Ni: 3.3%, Co: 0.45%, Si: 0.9%, Mg: 0.06%, Ti: 0.017%, and rare earth elements: 0.05%.
[0059] Smelting: First, add copper as a base, then add electrolytic copper plates and pure cobalt, followed by a slag remover. Once the molten copper is fully melted, cover with graphite powder. Then, add a small amount of copper-magnesium master alloy (20wt% magnesium content) for deoxidation, followed by the complete set of copper-silicon master alloy (20wt% silicon content). Heat to the smelting temperature of 1200℃, stir for 5 minutes, let stand for 15 minutes, take samples for composition analysis, and adjust the composition according to the analysis results. After composition adjustment, remove slag, degas for 30 minutes, let stand for 15 minutes, and then begin casting.
[0060] Casting: The crystallizer is made of copper or graphite; the casting speed is 70 mm / min; the casting temperature is 1200℃; and the primary cooling water flow rate is 70 m³ / min. 3 / h, secondary cooling water flow rate 7m 3 / h, during the casting process, titanium flasks (titanium content 30wt%) and rare earth elements are continuously added to the flow channel.
[0061] Sawing: Cut approximately 400mm from the top of the ingot.
[0062] Hot rolling: The ingot is heated in a walking beam furnace from room temperature to 950°C, held for 3 hours, and exited at 840°C. It is rolled in 7 passes and the final rolling temperature is 750°C. The total processing rate is 95%.
[0063] Milling: The strip obtained after hot rolling is milled, with 1.5 mm milled on the top and bottom sides and 1.0 mm milled on the width sides.
[0064] Cold rolling: The strip blank after milling is cold rolled, with a processing rate of about 90%.
[0065] Trimming: Trim the edges of the cold-rolled strip by about 5mm on each side.
[0066] Low-temperature tension annealing before solution treatment: temperature 400℃, speed 35m / min, tension 9kg / mm 2 .
[0067] One-time online solution treatment: The strip passes through at a speed of 20 m / min within a temperature range of 1050℃ and is rapidly cooled to obtain a supersaturated solid solution.
[0068] Cold rolling: The solution-treated strip is further cold rolled, with the cold rolling rate controlled at 50%.
[0069] Secondary online solution treatment: The solution temperature is 750℃ and the speed is 75m / min to obtain the final product.
[0070] Aging: After solution treatment, aging is carried out at 450℃ for 8 hours.
[0071] Cleaning: Clean the aged rolls to remove the surface oxide scale.
[0072] Cold rolling: The cleaned coil is cold rolled, with a processing rate of 25%.
[0073] Low-temperature tension annealing of finished products: temperature 425℃, speed 42m / min, tension 6kg / mm 2 The high-performance, low residual stress Cu-Ni-Co-Si alloy plate of Example 3 was obtained.
[0074] Example 4:
[0075] Ingredients: Raw materials are prepared according to the required weight ratio: Ni: 3.3%, Co: 0.3%, Si: 0.9%, Mg: 0.06%, Ti: 0.017%, and rare earth elements: 0.05%.
[0076] Smelting: First, add copper as a base, then add electrolytic copper plates and pure cobalt, followed by a slag remover. Once the molten copper is fully melted, cover with graphite powder. Then, add a small amount of copper-magnesium master alloy (20wt% magnesium content) for deoxidation, followed by the complete set of copper-silicon master alloy (20wt% silicon content). Heat to the smelting temperature of 1200℃, stir for 5 minutes, let stand for 15 minutes, take samples for composition analysis, and adjust the composition according to the analysis results. After composition adjustment, remove slag, degas for 30 minutes, let stand for 15 minutes, and then begin casting.
[0077] Casting: The crystallizer is made of copper or graphite; the casting speed is 70 mm / min; the casting temperature is 1200℃; and the primary cooling water flow rate is 70 m³ / min. 3 / h, secondary cooling water flow rate 7m 3 / h, during the casting process, titanium flasks (titanium content 30wt%) and rare earth elements are continuously added to the flow channel.
[0078] Sawing: Cut approximately 400mm from the top of the ingot.
[0079] Hot rolling: The ingot is heated in a walking beam furnace from room temperature to 950°C, held for 3 hours, and exited at 840°C. It is rolled in 7 passes and the final rolling temperature is 750°C. The total processing rate is 95%.
[0080] Milling: The strip obtained after hot rolling is milled, with 1.5 mm milled on the top and bottom sides and 1.0 mm milled on the width sides.
[0081] Cold rolling: The strip blank after milling is cold rolled, with a processing rate of about 90%.
[0082] Trimming: Trim the edges of the cold-rolled strip by about 5mm on each side.
[0083] Low-temperature tension annealing before solution treatment: temperature 450℃, speed 45m / min, tension 5kg / mm 2 .
[0084] One-time online solution treatment: The strip passes through at a speed of 20 m / min within a temperature range of 1050℃ and is rapidly cooled to obtain a supersaturated solid solution.
[0085] Cold rolling: The solution-treated strip is further cold rolled, with the cold rolling rate controlled at 50%.
[0086] Secondary online solution treatment: The solution temperature is 750℃ and the speed is 75m / min to obtain the final product.
[0087] Aging: After solution treatment, aging is carried out at 450℃ for 8 hours.
[0088] Cleaning: Clean the aged rolls to remove the surface oxide scale.
[0089] Cold rolling: The cleaned coil is cold rolled, with a processing rate of 25%.
[0090] Low-temperature tension annealing of finished products: temperature 425℃, speed 42m / min, tension 6kg / mm 2 Thus, the high-performance, low residual stress Cu-Ni-Co-Si alloy plate of Example 4 was obtained.
[0091] Example 5:
[0092] Ingredients: Raw materials are prepared according to the required weight ratio: Ni: 2.3%, Co: 0.1%, Si: 0.6%, Mg: 0.01%, Ti: 0.01%, and rare earth elements: 0.1%.
[0093] Smelting: First, add copper as a base, then add electrolytic copper plates and pure cobalt, followed by a slag remover. Once the molten copper is fully melted, cover with graphite powder. Then, add a small amount of copper-magnesium master alloy (20wt% magnesium content) for deoxidation, followed by the complete set of copper-silicon master alloy (20wt% silicon content). Heat to the smelting temperature of 1200℃, stir for 5 minutes, let stand for 15 minutes, take samples for composition analysis, and adjust the composition according to the analysis results. After composition adjustment, remove slag, degas for 30 minutes, let stand for 15 minutes, and then begin casting.
[0094] Casting: The crystallizer is made of copper or graphite; the casting speed is 70 mm / min; the casting temperature is 1200℃; and the primary cooling water flow rate is 70 m³ / min. 3 / h, secondary cooling water flow rate 7m 3 / h, during the casting process, titanium flasks (titanium content 30wt%) and rare earth elements are continuously added to the flow channel.
[0095] Sawing: Cut approximately 400mm from the top of the ingot.
[0096] Hot rolling: The ingot is heated in a walking beam furnace from room temperature to 950°C, held for 3 hours, and exited at 840°C. It is rolled in 7 passes and the final rolling temperature is 750°C. The total processing rate is 95%.
[0097] Milling: The strip obtained after hot rolling is milled, with 1.5 mm milled on the top and bottom sides and 1.0 mm milled on the width sides.
[0098] Cold rolling: The strip blank after milling is cold rolled, with a processing rate of about 90%.
[0099] Trimming: Trim the edges of the cold-rolled strip by about 5mm on each side.
[0100] Low-temperature tension annealing before solution treatment: temperature 450℃, speed 45m / min, tension 5kg / mm 2 .
[0101] One-time online solution treatment: The strip passes through at a speed of 35 m / min within a temperature range of 1100℃ and is rapidly cooled to obtain a supersaturated solid solution.
[0102] Cold rolling: The solution-treated strip is further cold rolled, with the cold rolling rate controlled at 50%.
[0103] Secondary online solution treatment: The solution temperature is 850℃ and the speed is 90m / min to obtain the final product.
[0104] Aging: After solution treatment, aging is carried out at 500℃ for 6 hours.
[0105] Cleaning: Clean the aged rolls to remove the surface oxide scale.
[0106] Cold rolling: The cleaned coil is cold rolled, with a processing rate of 25%.
[0107] Low-temperature tension annealing of finished products: temperature 500℃, speed 55m / min, tension 9kg / mm 2 Thus, the high-performance, low residual stress Cu-Ni-Co-Si alloy plate of Example 5 was obtained.
[0108] The present invention also includes Comparative Examples 1 to 27, which, based on Examples 1, 2, 3, 4, or 5, respectively, change a single component parameter or process parameter to exceed the range defined by the present invention, while keeping other conditions unchanged, to illustrate the influence of the component range and process parameter range defined by the present invention on the comprehensive performance of alloy plates.
[0109] Comparative Example 1: The difference from Example 1 is that the Ni content is too low and the (Ni+Co) / Si ratio is too low.
[0110] Comparative Example 2: The difference from Example 2 is that the Ni content is too high and the (Ni+Co) / Si ratio is too high.
[0111] Comparative Example 3: The difference from Example 1 is that the Co content is too low and the (Ni+Co) / Si ratio is too low.
[0112] Comparative Example 4: The difference from Example 2 is that the Co content is too high, and the (Ni+Co) / Si ratio is too high.
[0113] Comparative Example 5: The difference from Example 1 is that only 0.02% Ti is added.
[0114] Comparative Example 6: The difference from Example 1 is that only 0.02% Mg is added.
[0115] Comparative Example 7: The difference from Example 2 is that the Mg content is too high.
[0116] Comparative Example 8: The difference from Example 2 is that the Ti content is too high.
[0117] Comparative Example 9: The difference from Example 2 is that the rare earth content is too high.
[0118] Comparative Example 10: The difference from Example 1 is that the low-temperature tension annealing temperature before the first solution treatment is too low.
[0119] Comparative Example 11: The difference from Example 1 is that the low-temperature tension annealing temperature before the first solution treatment is too high.
[0120] Comparative Example 12: The difference from Example 2 is that the low-temperature tension annealing rate before the first solution treatment is too slow.
[0121] Comparative Example 13: The difference from Example 2 is that the low-temperature tension annealing rate before the first solution treatment is too fast.
[0122] Comparative Example 14: The difference from Example 3 is that the solution temperature was too high in the first step.
[0123] Comparative Example 15: The difference from Example 3 is that the solution temperature was too low in the first step.
[0124] Comparative Example 16: The difference from Example 4 is that the secondary solution temperature is too high.
[0125] Comparative Example 17: The difference from Example 4 is that the secondary solution temperature is too low.
[0126] Comparative Example 18: The difference from Example 3 is that the solution solution rate is too fast in one step.
[0127] Comparative Example 19: The difference from Example 3 is that the solution treatment rate is too slow in one step.
[0128] Comparative Example 20: The difference from Example 4 is that the secondary solution solution rate is too fast.
[0129] Comparative Example 21: The difference from Example 4 is that the secondary solution rate is too slow.
[0130] Comparative Example 22: The difference from Example 5 is that the low-temperature tension annealing temperature of the finished product is too high.
[0131] Comparative Example 23: The difference from Example 5 is that the low-temperature tension annealing temperature of the finished product is too low.
[0132] Comparative Example 24: The difference from Example 2 is that the low-temperature tension annealing speed of the finished product is too fast.
[0133] Comparative Example 25: The difference from Example 2 is that the low-temperature tension annealing speed of the finished product is too slow.
[0134] Comparative Example 26: The difference from Example 5 is that the low-temperature tension annealing of the finished product has excessive tension.
[0135] Comparative Example 27: The difference from Example 5 is that the low-temperature tension annealing tension of the finished product is too small.
[0136] The alloy composition formulations for the examples and comparative examples are shown in Table 1 below: Table 1 Alloy composition formulations of the examples and comparative examples
[0137] The processes for the embodiments and comparative examples are shown in Table 2 below: Table 2. Processes of the Examples and Comparative Examples
[0138] The performance test results of the examples and comparative examples are shown in Table 3 below: Table 3 Performance test results of the examples and comparative examples
[0139] As can be seen from Tables 1, 2, and 3: In Example 1, the Cu-Ni-Co-Si alloy, with the addition of Mg and Ti microalloying elements, achieves a hardness of 289 HV, conductivity of 41.03% IACS, residual stress of -35 MPa, grain size ≤0.01 mm, tensile strength of 994 MPa, yield strength of 942 MPa, 90° bending R / t=0, and 180° bending R / t=2.5. The alloy undergoes low-temperature tension annealing before the first solution treatment, followed by two solution treatment processes, resulting in synergistic optimization of properties and microstructure.
[0140] In Example 2, the Cu-Ni-Co-Si alloy, with the addition of Mg, Ti microalloying elements and rare earth elements, achieves a hardness of 323 HV, conductivity of 36.64% IACS, residual stress of -45 MPa, grain size ≤0.01 mm, tensile strength of 1040 MPa, yield strength of 951 MPa, 90° bending R / t=0, and 180° bending R / t=2.5. The alloy undergoes low-temperature tension annealing before the first solution treatment, followed by two solution treatment processes, resulting in synergistic optimization of performance and microstructure.
[0141] In Example 3, the Cu-Ni-Co-Si alloy, with the addition of Mg, Ti microalloying elements and rare earth elements, achieves a hardness of 313 HV, conductivity of 39.35% IACS, residual stress of -45 MPa, grain size ≤0.01 mm, tensile strength of 1002 MPa, yield strength of 947 MPa, 90° bending R / t=0, and 180° bending R / t=2.5. The alloy undergoes low-temperature tension annealing before the first solution treatment, followed by two solution treatment processes, resulting in synergistic optimization of performance and microstructure.
[0142] In Example 4, the Cu-Ni-Co-Si alloy, with the addition of Mg, Ti microalloying elements and rare earth elements, achieves a hardness of 312 HV, conductivity of 38.57% IACS, residual stress of -29 MPa, grain size ≤0.01 mm, tensile strength of 990 MPa, yield strength of 941 MPa, 90° bending R / t=0, and 180° bending R / t=2.5. The alloy undergoes low-temperature tension annealing before the first solution treatment, followed by two solution treatment processes, resulting in synergistic optimization of performance and microstructure.
[0143] In Example 5, the Cu-Ni-Co-Si alloy, with the addition of Mg, Ti microalloying elements and rare earth elements, achieves a hardness of 295 HV, conductivity of 41.83% IACS, residual stress of -33 MPa, grain size ≤0.01 mm, tensile strength of 999 MPa, yield strength of 947 MPa, 90° bending R / t=0, and 180° bending R / t=2.5. The alloy undergoes low-temperature tension annealing before the first solution treatment, followed by two solution treatment processes, resulting in synergistic optimization of performance and microstructure.
[0144] As can be seen from the above examples and comparative examples: In Example 1, the Cu-Ni-Co-Si alloy, with the addition of Mg and Ti microalloying elements but without the addition of rare earth elements, can achieve a hardness of 289 HV, a conductivity of 41.03% IACS, a residual stress of -35 MPa, a grain size ≤0.01 mm, a tensile strength of 994 MPa, a yield strength of 942 MPa, a 90° bending R / t=0, and a 180° bending R / t=2.5; In Examples 2 to 5, C By adding Mg and Ti microalloying elements and further adding different amounts of rare earth elements to the u-Ni-Co-Si alloy, it is possible to maintain a hardness of 312~323HV, conductivity of 36.64%~41.83%IACS, tensile strength of 990~1040MPa, yield strength of 941~951MPa, 90° bending R / t=0, and 180° bending R / t=2.5, while controlling the residual stress within the range of -45~-29MPa. These results demonstrate that this invention, through precise control of the content and ratio of Ni, Co, Si, Mg, Ti, and rare earth elements, combined with a synergistic process of low-temperature tension annealing before solution treatment, two online solution treatments, and low-temperature tension annealing of the finished product, can stably obtain Cu-Ni-Co-Si alloy sheets that possess high strength, high conductivity, excellent bending performance, and low residual stress.
[0145] In Comparative Example 1, the Ni content was too low, and the (Ni+Co) / Si ratio was too low, resulting in low alloy strength and a significant decrease in electrical conductivity.
[0146] In Comparative Example 2, the Ni content was too high, and the (Ni+Co) / Si ratio was too high, which led to a decrease in alloy strength, electrical conductivity, and bending performance.
[0147] In Comparative Example 3, the Co content was too low, and the (Ni+Co) / Si ratio was too low, which led to a decrease in alloy strength, electrical conductivity, and bending performance.
[0148] In Comparative Example 4, the Co content was too high and the (Ni+Co) / Si ratio was too low, which led to a decrease in alloy strength, electrical conductivity, and bending performance.
[0149] In Comparative Example 5, the strength decreased when only 0.02% Ti was added.
[0150] In Comparative Example 6, the strength decreased when only 0.02% Mg was added.
[0151] In Comparative Example 7, the Mg content was too high, resulting in decreased bending performance.
[0152] In Comparative Example 8, the high Ti content resulted in decreased electrical conductivity.
[0153] In Comparative Example 9, the rare earth content was too high, resulting in poor bending performance.
[0154] In Comparative Example 10, the low-temperature tension annealing temperature before the first solution treatment was low, resulting in a larger grain size compared to Example 1.
[0155] In Comparative Example 11, the low-temperature tension annealing temperature before the first solution treatment was high, resulting in reduced strength and larger grain size compared to Example 1.
[0156] In Comparative Example 12, the low-temperature tension annealing rate before the first solution treatment was too slow, resulting in a decrease in strength compared to Example 2.
[0157] In Comparative Example 13, the low-temperature tension annealing rate before the first solution treatment was too fast, resulting in a larger grain size compared to Example 2.
[0158] In Comparative Example 14, the initial solution temperature was higher, resulting in larger grain size and reduced bending performance compared to Example 3.
[0159] In Comparative Example 15, the initial solution temperature was low, resulting in reduced strength compared to Example 3.
[0160] In Comparative Example 16, the secondary solution temperature was high, resulting in larger grain size, reduced strength, and decreased bending performance compared to Example 4.
[0161] In Comparative Example 17, the secondary solution temperature was high, and compared with Example 4, the grains were still fibrous, resulting in reduced bending performance.
[0162] In Comparative Example 18, the solution treatment rate was too fast, resulting in a decrease in strength compared to Example 3.
[0163] In Comparative Example 19, the solution treatment rate was too slow, resulting in reduced strength, larger grain size, and reduced bending performance compared to Example 3.
[0164] In Comparative Example 20, the secondary solution temperature was faster, and compared with Example 4, the grains were still fibrous, resulting in reduced bending performance.
[0165] In Comparative Example 21, the secondary solution temperature was slow, resulting in larger grains, reduced strength, and decreased bending performance compared to Example 4.
[0166] In Comparative Example 22, the finished product had a higher low-temperature tension annealing temperature, resulting in a decrease in strength compared to Example 5.
[0167] In Comparative Example 23, the finished product underwent a lower low-temperature tension annealing temperature, resulting in greater residual stress compared to Example 5.
[0168] In Comparative Example 24, the finished product underwent rapid low-temperature tension annealing, resulting in greater residual stress compared to Example 2.
[0169] In Comparative Example 25, the finished product underwent slow low-temperature tension annealing, resulting in reduced strength compared to Example 2.
[0170] In Comparative Example 26, the finished product underwent high low-temperature tension annealing, resulting in greater residual stress compared to Example 5.
[0171] In Comparative Example 27, the finished product underwent low-temperature tension annealing with low tension, resulting in greater residual stress compared to Example 5.
[0172] The results of Comparative Examples 1 to 27 show that whether the compositional parameters (such as the content of Ni, Co, and Si and the (Ni+Co) / Si ratio, the content of Mg, Ti, and rare earth elements) exceed the limits of this invention, or the process parameters (such as the temperature, speed, and tension of low-temperature tension annealing, primary solution treatment, secondary solution treatment, and finished product annealing) exceed the limits of this invention, one or more of the following properties of the alloy sheet will deteriorate to varying degrees: strength, conductivity, grain size, bending performance, or residual stress. This makes it impossible to simultaneously meet the comprehensive performance requirements of tensile strength ≥990 MPa, yield strength ≥940 MPa, conductivity ≥36% IACS, grain size ≤0.01 mm, 90° bending R / t ≤0.5, and residual stress within ±50 MPa. This further verifies the rationality and necessity of the compositional and process parameter ranges defined in this invention.
[0173] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A high-performance, low-residual-stress Cu-Ni-Co-Si alloy plate, characterized in that, The chemical composition of the alloy plate, by weight percentage, is: Ni 2.3%~4.6%, Co 0.1%~0.8%, Si 0.6%~1.3%, Mg 0.01%~0.12%, Ti 0.01%~0.025%, rare earth elements 0~0.1%, and the balance being Cu and unavoidable impurities; wherein the rare earth elements are one or more of La, Ce, and Y; and satisfy (Ni+Co) / Si=4~4.
2.
2. The high-performance, low residual stress Cu-Ni-Co-Si alloy plate according to claim 1, characterized in that, The alloy sheet has a hardness of 270~330HV, conductivity ≥36%IACS, grain size ≤0.01mm, tensile strength ≥990MPa, yield strength ≥940MPa, R / t ≤0.5 in the GW and BW directions of a 90° bend, R / t ≤2.5 in the GW and BW directions of a 180° bend, and residual stress controlled within ±50MPa.
3. The high-performance, low residual stress Cu-Ni-Co-Si alloy plate according to claim 2, characterized in that, The alloy plate has a thickness of 0.03~0.8mm and a width of 550~600mm.
4. The high-performance, low residual stress Cu-Ni-Co-Si alloy plate according to claim 1, characterized in that, The alloy sheet undergoes aging treatment to precipitate a second phase inside, followed by cold rolling to cause internal dislocations to multiply. The dislocations interact with the second phase to form a stable dislocation cell structure.
5. The high-performance, low residual stress Cu-Ni-Co-Si alloy plate according to claim 1, characterized in that, By weight percentage, Ni is 3.3%~4.6%, Co is 0.3%~0.8%, Si is 0.9%~1.3%, Mg is 0.06%~0.12%, Ti is 0.017%~0.025%, and rare earth elements are 0.05%~0.1%.
6. The high-performance, low residual stress Cu-Ni-Co-Si alloy plate according to claim 1, characterized in that, The specifications of the ingots used to prepare the alloy plate are: width ≥ 610 mm and thickness ≥ 150 mm.
7. A method for preparing a high-performance, low residual stress Cu-Ni-Co-Si alloy plate as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Ingredients: Prepare raw materials according to the chemical composition and weight percentage of the high-performance, low residual stress Cu-Ni-Co-Si alloy plate. S2. Smelting: Lay a layer of copper at the bottom, add electrolytic copper plates and pure cobalt, add slag remover, and after the copper is fully smelted, cover with graphite powder. Then add a copper-magnesium master alloy with a magnesium content of 20wt% for deoxidation, and then add all the prepared copper-silicon master alloy with a silicon content of 20wt%. Raise the temperature to the smelting temperature of 1200~1300℃, stir for 3~5 minutes, let stand for 10~15 minutes, take a sample to test the composition, and adjust the composition according to the test results. After adjusting the composition, remove slag and degas for 20~30 minutes, let stand for 10~15 minutes, and then start casting. S3. Casting: The crystallizer is made of copper or graphite; the casting speed is 70~110 mm / min; the casting temperature is 1200~1250℃; and the primary cooling water flow rate is 40~70 m³ / min. 3 / h, secondary cooling water flow rate 4~7m 3 / h; During the casting process, a titanium ladle with a titanium content of 30wt% and the aforementioned rare earth elements are continuously added to the flow channel to obtain an ingot; S4. Sawing: Cut the head of the ingot by 200~400mm; S5. Hot rolling: The ingot is heated in a walking beam furnace from room temperature to 950~1050℃, held for 3~5 hours, and the furnace exit temperature is 840~880℃. It is rolled 7~9 times, and the final rolling temperature is 600~750℃. The total processing rate is 90%~95%, and hot-rolled strip is obtained. S6. Milling: Mill the surface of the hot-rolled strip blank, with a milling depth of 0.5~1.5mm on each of the upper and lower sides and 0.3~1.0mm on each of the width sides; S7. Cold rolling: Cold rolling is performed on the milled strip blank, with a processing rate of 85%~90%; S8. Trimming: Trimming is performed on both sides of the cold-rolled strip blank, removing 5~10mm from each side to obtain the trimmed strip. S9. Low-temperature tension annealing before solution treatment: The strip blank after trimming is subjected to low-temperature tension annealing at a temperature of 350~450℃, a speed of 15~45m / min, and a tension of 2~9kg / mm. 2 ; S10, One-time online solution treatment: The strip after step S9 is subjected to high-temperature solution treatment, passing through a temperature range of 950~1100℃ at a speed of 5~35m / min and rapidly cooled to obtain a supersaturated solid solution; S11. Cold rolling: The solution-treated strip is further cold-rolled, with the cold rolling rate controlled at 30%~80%. S12, Secondary online solution treatment: The strip after cold rolling in step S11 is subjected to online solution treatment at a temperature of 650~850℃ and a speed of 60~90m / min. S13. Aging: The strip after solution treatment in step S12 is subjected to aging treatment at a temperature of 400~500℃ for 6~12 hours. S14. Cleaning: Clean the aged strip to remove surface oxide scale; S15, Cold rolling: Cold rolling is performed on the cleaned strip, with a processing rate of 15%~40%; S16. Low-temperature tension annealing of finished product: The strip cold-rolled in step S15 is subjected to low-temperature tension annealing at a temperature of 350~500℃, a speed of 30~55m / min, and a tension of 4~9kg / mm. 2 The high-performance, low residual stress Cu-Ni-Co-Si alloy plate was obtained.
8. The preparation method according to claim 7, characterized in that: The low-temperature tension annealing described in step S9 brings the strip, which is in a work-hardened state after high-processing-rate cold rolling, back to a recovery state before recrystallization. The point defects and dislocations inside the material rearrange and partially cancel each other out, gradually releasing the uneven deformation storage energy, reducing the overall driving force of subsequent high-temperature solid solution, and making the grain size more uniform.
9. The preparation method according to claim 7, characterized in that: The first online solution in step S10 is a high-temperature solution to make the material reach a supersaturated state, so as to ensure that the subsequent aging process can fully precipitate and obtain higher performance; the second online solution in step S12 is a low-temperature rapid solution, so that the material does not have time to precipitate the second phase, while controlling the grain size to ≤0.01mm.
10. The preparation method according to claim 7, characterized in that: In step S16, the low-temperature tension annealing of the finished product, under the synergistic effect of temperature and tension, controls the residual stress of the alloy sheet within ±50MPa, suppressing torsional deformation during the stamping process.